حق الرجوع على الشريك في المال الشائع في حالة الانتفاع والتصرف - عبدالرضا حسين عبدالله; صالح قتيبة مهدي (Journal of Legal Sciences, 2017)
The subject of the right of return on partner on common property in the case of the use and disposition from the important subjects in the real property rights, the importance lies through by identifying the band which Allows by law to the partner initiate authorities which conferred him of the right of ownership to share common if the low is not allowed to exceed this range by any partner because it infects the right of others partners hence arises it is then established to the other partner right back to the infringer Partner. Through find the subject of study show cases which form infringement of the other partner and form this cases have a partner the right of return to the other partner who benefited or disposal in property common which is permitted by law. The common partner if he was allows by the law to use his common share and exploited and dispose of them .that is showed be in legal limits which means it showed be amount the common share if the partner utilize or acted by or more than his common share or all the common property or caused by directly authority of the use and disposition in damage for the rest of the partners in such cases was to the another partner directly his share stake in the back overtaking or cause.